IMPLEMENTASI KONSEP KEBIJAKAN ONE BELT ONE ROAD (OBOR) CHINA DALAM KERANGKA KERJASAMA PEMBANGUNAN INFRASTUKTUR DI INDONESIA - Muhammad Fahrizal (Journal of Diplomacy and International Studies, 2019)
This article discusses the One Belt One Road OBOR Initiative launched by Xi Jinping in 2013, focusing on the role of the initiative in realizing Zhongguomeng. The OBOR initiative is a new infrastructure development project that uses the concept of the New Silk Road that covers geopolitical and geo-economic aspects to connect the Eurasian region with China as its center. The author begins the research by interpreting the background that prompted the Chinese government to implement the OBOR Initiative using historical approaches and qualitative studies, then analyzing the extent to which the OBOR policy can be useful for Xi Jinping to achieve the Zhongguomeng target. The Silk Road was later promoted to become China's new slogan in various international forums. In the view of the current Chinese leader, the concept of the New Silk Road is also known as the "One Belt One Road". China then added another concept, the 21st Century Maritime Silk Road which was seen as an effort to strengthen relations with countries in South and Southeast Asia including one with Indonesia which focused on maritime trade and acceleration. infrastructure development in order to increase economic growth. The results show that the OBOR Initiative has a role as a tool to realize Zhongguomeng through the development of infrastructure that supports the flow of industrial trade, provides a unifying platform for China, and global peace cooperation relations. Indonesia as a developing country is one of the OBOR member countries to improve its economy. In its implementation, infrastructure cooperation between the two countries continues to increase which has a significant impact on Indonesia's infrastructure development, although it cannot be denied that there are many obstacles that need to be faced